A double demodulation algorithm for narrow spectral features - Ragaini, Enrico (1995)
This paper proposes a technique for processing signals in which the relevant feature consists of the shape and position of narrow doppler spectral lines. The proposed technique is the digital version of a quadrature demodulator, and its purpose is to demodulate a selected spectral line allowing to study its envelope as a slowly varying process.